Comparison of corneal biomechanics after myopic small-incision lenticule extraction compared to LASIK: an ex vivo study - Kanellopoulos AJ (Clinical Ophthalmology, 2018)
Anastasios John Kanellopoulos1,2 1Department of Ophthalmology, Laservision Clinical and Research Institute, Athens, Greece; 2Department of Ophthalmology, New York University Medical School, New York, NY, USA Purpose: To investigate ex vivo potentially different corneal biomechanical properties after small-incision lenticule extraction (SMILE) versus LASIK for myopic correction.Methods: Thirty human donor corneas were subjected to either myopic SMILE or femtosecond laser-assisted LASIK. Donor corneas were assigned to six investigative groups: Group A, –3.00 D (diopters) SMILE; Group B, –8.00 D SMILE; Group C, –3.00 D LASIK; and Group D, –8.00 D LASIK. Additionally, two control groups were formed: Group E, SMILE and Group F, LASIK. All groups consisted of five corneas, randomly allocated. The corneas in the control groups were subjected to the corresponding femtosecond-laser lamellar cuts but not to tissue removal. Evaluation of biomechanical tensile strength was conducted by biaxial force application. Primary outcome measures were stress at 10% and 15% strain, and Young’s modulus at 10% and 15% strain.Results: In SMILE, the average relative difference (Δ) of the four outcome measures was –34.46% for –3.00 D correction versus control Group E and –49.34% for –8.00 D correction versus control Group E. In LASIK, average Δ was –24.88% for –3.00 D correction versus control, and –52.73% for –8.00 D correction versus control. All these differences were statistically significant; SMILE compared to LASIK for the same myopic correction appears to result in more biomechanical reduction for –3.00 D corrections by –26%, while a nonstatistically significant difference was noted in –8.00 D corrections.Conclusion: Both SMILE and LASIK procedures do substantially alter corneal biomechanical properties, and the degree of tensile strength reduction is statistically significantly correlated to the extent of myopic correction. Additionally, SMILE procedure seems to result in more tensile strength reduction in lower myopic corrections compared to LASIK, and similar tensile strength reduction to LASIK in higher myopic corrections when compared to LASIK. Keywords: SMILE, femto-second LASIK, myopic LASIK, corneal biomechanics, Young’s modulus, corneal stress–strain, shear strength, tensile strength